Ecotoxicity assessment using ciliate cells in millifluidic droplets - Illing, Rico; Burkart, Corinna; Pfitzner, Daniel; Jungmann, Dirk; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Biomicrofluidics, 2016)
Precise analysis of the aquatic cells and their responses to the toxic chemicals, i.e., water disinfective agents, is of crucial importance due to their role in the ecosystem. We demonstrate the application of the droplets based millifluidic tool for isolating and longtime monitoring of single Paramecium tetraurelia cells using a large number of water-in-oil emulsion droplets. Due to the automated monitoring of the fluorescence signal, the droplets containing cells are distinguished from the empty reservoirs. A viability indicator is used to follow the metabolic dynamic of the cells in every single droplet. Finally, we perform ecotoxicity tests in droplets, exposing the encapsulated paramecia cells to silver nitrate for determination of EC50 levels, and compare the output with the conventional microtiter plate assay.
CRIS-Team Scopus Importer:2023-03-20